Особливості росту і розвитку Silphium perfoliatum L. у перший рік вегетації в зв’язку з інтродукцією в Лісостепу України - Abramov, A.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 1999)
Growth and development of Silphium perfoliatum L. in the first vegetation year in connection with introduction in the Forest-Steppe of Ukraine have been investigated. Regularities of vegetative organs growth depending on the date of sowing is established.